1996
DOI: 10.1210/jcem.81.2.8636276
|View full text |Cite
|
Sign up to set email alerts
|

Differences in bone and vitamin D metabolism between primary hyperparathyroidism and malignancy-associated hypercalcemia.

Abstract: Bone and vitamin D metabolism are examined in patients with primary hyperparathyroidism (1 degree HPT), humoral hypercalcemia of malignancy (HHM), and local osteolytic hypercalcemia (LOH) with normal renal function. Among the bone resorption markers, T scores of total deoxypyridinoline (Dpyd) were highest in HHM and were significantly higher than those in 1 degree HPT. Among the formation markers, T scores of osteocalcin (OC) were highest in 1 degree HPT but were negative in HHM. The elevation in total Dpyd wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Secondly, while both syndromes have marked increases in osteoclastic bone resorption, many patients with HHM do not have the normally coupled increase in osteoblastic activity that those with 1 HPT experience. Studies using either serum markers of bone turnover (Nakayama et al 1996) or quantitative bone histomorphometry (Stewart et al 1982) have demonstrated this uncoupling of bone resorption from bone formation. Finally, unlike the metabolic acidosis seen in patients with 1 HPT, patients with HHM often have a metabolic alkalosis with a low plasma chloride and high plasma bicarbonate concentration.…”
Section: Hhm Vsmentioning
confidence: 99%
“…Secondly, while both syndromes have marked increases in osteoclastic bone resorption, many patients with HHM do not have the normally coupled increase in osteoblastic activity that those with 1 HPT experience. Studies using either serum markers of bone turnover (Nakayama et al 1996) or quantitative bone histomorphometry (Stewart et al 1982) have demonstrated this uncoupling of bone resorption from bone formation. Finally, unlike the metabolic acidosis seen in patients with 1 HPT, patients with HHM often have a metabolic alkalosis with a low plasma chloride and high plasma bicarbonate concentration.…”
Section: Hhm Vsmentioning
confidence: 99%
“…The normal physiologic role of PTHrP is not thoroughly understood, but it is considered to be involved in normal calcium homeostasis (18), regulation of smooth muscle (19), and regulation of tissue and organ development, differentiation, and proliferation (1-3, 20, 21 , , , and (27). In the patients with HHB, the serum 1,25-dihydroxy vitamin D3 concentration was reported to be low or normal (6,10,12 …”
Section: In 1979 Stewart Et Al First Used the Term "Humoral Hypercalmentioning
confidence: 99%
“…Bone metabolic markers were examined in the same laboratory as previously reported (5) with a high-performance liquid chromatography (HPLC) method for urinary total deoxypyridinoline and pyridinoline, (10) an immunoassay using Osteomark NTx (Mochida Pharmaceutical Co., Tokyo, Japan) for urinary N-telopeptide of type I collagen (NTx), an immunoradiometric assay using a Mitsubishi bone-gla protein (BGP)-IRMA kit (Mitsubishi Kagaku) for serum osteocalcin (5) and an immunoassay using Alkphase-B kit (Quidel, San Diego, CA, USA) for serum bone-type alkaline phosphatase. For bone resorption markers, urinary excretions of deoxypyridinoline (74 pmol/mol of creatinine [2.2-6.1]) and pyridinoline (333 pmol/mol of creatinine [17.7-41.9]) were elevated at the time of diagnosis, and that of NTx was higher (87.7 nmol of bone collagen equivalents [BCE]/mmol of creatinine [Ͻ55]) 7 years after diagnosis even in the midst of regular infusions of incadronate.…”
Section: Bone Metabolic Markersmentioning
confidence: 99%
“…Serum 1,25-dihydroxyvitamin D is suppressed usually in HHM patients, whereas its level is elevated in primary hyperparathyroidism. (1,5) Bone resorption and formation are well balanced in primary hyperparathyroidism, whereas bone resorption is enhanced but bone formation is severely suppressed in HHM. (5,6) It is not clarified whether there are any systemic effects of PTHrP that are different from those of PTH or there are other humoral factors than PTHrP in HHM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation